The Effect of PQ4R (Preview, Question, Read, Reflect, Recite, Review) Learning Method with Internet-Assisted on Learning Outcomes of Students SMA Labschool UNTAD Palu on Salt Hydrolysis - Ersa W. Lakukua; Mery Napitupulu; Afadil Afadil (Universitas Tadulako, 2020)
This study aimed to describe the effect of PQ4R learning methods with internet-assisted on students’ learning outcomes of class XI SMA Labschool UNTAD Palu on salt hydrolysis material. The type of research was quasi-experimental with a nonrandomized pretest-posttest control group design. This study was conducted with two groups, namely the XI IPA class 1 as the experimental group (n = 21) and the XI IPA class 3 as a control group (n = 23). The testing of the research data used a two-party t-test statistical analysis. The results of data analysis obtained that the average of an experimental class was 63.19 with a standard deviation of 7.37 and a control class was 57.22 with a standard deviation of 8.19. The results of testing the hypothesis with the two-party t-test statistics obtained -ttable<tcount> +ttable (tcount 2.54 and ttable 1.68) with a significance level (α) = 0.05 and degrees of freedom (dk) = 35. Based on the results testing of the hypothesis, it can be concluded that H0 was rejected and H1 was accepted. This means that the PQ4R learning method with internet-assisted has a positive effect on the learning outcomes of students class XI SMA Labschool UNTAD Palu.